Intersecting Shalawat And Church Music On Spiritual Sweetness And Pop Culture - rahman, luthfi; Lail, Moh Jamalul; Mawardi, Imam (AL-ADYAN, 2024)
This article examines the tradition of prayer/Shalawat as a way to get closer to the Prophet Muhammad and Allah. Over time, this prayer practice developed alongside the use of traditional musical instruments like terbang, jidor, teplak and kricik. The article also looks at how Christians incorporate various songs into their worship services as a form of prayer and connection with God. The research aims to understand how music deepens the meaning and impact of prayer for worshippers seeking closeness with the divine. It also wants to explore the spiritual significance of praying with or without instruments and how pop culture elements factor in. The qualitative study utilizes an exploratory-descriptive approach through a comparative theology lens. Key findings are twofold. First, for Muslims, prayer with Muhammad and Allah is a means for drawing nearer to them, obtaining help and healing. For Christians, music is viewed as a gift from God, an expression of thankfulness for life's joys, and encouragement and comfort during difficulties. Second, Islamic shalawat and Christian church music intersect with pop culture by blending traditional instruments like the terbang, jidor, teplak and kricik with contemporary tone and rhythm variations like dangdut. Here, pop culture represents a positive change because it strengthens the spiritual experience for worshippers while adding entertainment value.